Identity development in the adolescence and emergent adulthood: a comparison of global identity versus identity in specific domains - Zacarés González, Juan José; Iborra Cuéllar, Alejandro; Tomás Miguel, José Manuel; Serra Desfilis, Emilia (Anales de Psicología / Annals of Psychology, 2009)
The aims of this study were to examine the development and structure of identity across adolescence and the influence of the main social support sources and self-esteem in this process. Measures were taken in a sample of 283 young people between 14 and 22 years, including two measures of identity development (global identity and domain-specific identity, relational and school identity), perceived social support and global self-esteem. Results pointed out a progressive development of the identity, especially at the late adolescence and in school domain. Sex dif-ferences highlighted faster identity development in girls, both in relational and school domain. The moderate, but consistent, contribution of self-esteem and social support to identity development is also discussed. Peer social support is a decisive factor in identity development, more than parental support.